Poor Sleep Quality Related to Impaired Cognitive Function Following Stroke: A Comparative Cross-Sectional Study - Sofiani, Yani; Rahim Kamil, Abdu; Puspitasari, Nia Ayu; Hadi, Muhammad; Agung, Rizki Nugraha; Kurwiyah, Neneng (Universitas Aisyah Pringsewu, 2022)
Sleep deprivation is a common concern among stroke patients. There was a connection between sleep deprivation and poor cognitive function. Few studies, however, have compared sleep and cognitive variations in older adults with and without stroke, as well as explored the relationship between sleep quality and cognitive function. The objective of this study was to explore the quality and feature of sleep between patients with and without a stroke. To assess the association between sleep quality and cognitive dysfunction in older adults. A cross-sectional analysis was carried out. 156 participants completed this research. The study was carried out in 90 stroke patients and 66 of non-stroke patients. The patient was given a sleep quality questionnaire and took a cognitive test. In addition, a multivariate linear regression statistical analysis was used to determine the relationship between two variables. The global mean PSQI in patients with stroke was 7.12±3.96 versus 4.98±2.86, respectively, higher than the non-stroke group. Around 56.7 percent of stroke patients complained of poor sleep quality. Stroke patients scored lower than those who did not get a stroke on the memory and executive function test. Sleep quality affects memory by 28.6 percent. Poor sleep quality was strongly associated with memory dysfunction in stroke patients. To prevent patients with stroke from experiencing cognitive loss, health care providers should develop effective interventions to improve sleep quality. Kurang tidur adalah masalah umum di antara pasien stroke. Ada hubungan antara kurang tidur dan fungsi kognitif yang buruk. Beberapa penelitian, bagaimanapun, telah membandingkan variasi tidur dan kognitif pada orang dewasa yang lebih tua dengan dan tanpa stroke, serta mengeksplorasi hubungan antara kualitas tidur dan fungsi kognitif. Tujuan dari penelitian ini adalah untuk mengeksplorasi kualitas dan fitur tidur antara pasien dengan dan tanpa stroke. Untuk menilai hubungan antara kualitas tidur dan disfungsi kognitif pada orang dewasa yang lebih tua. Sebuah analisis cross-sectional dilakukan. 156 peserta menyelesaikan penelitian ini. Penelitian dilakukan pada 90 pasien stroke dan 66 pasien non stroke. Pasien diberi kuesioner kualitas tidur dan menjalani tes kognitif. Selain itu, analisis statistik regresi linier multivariat digunakan untuk mengetahui hubungan antara dua variabel. Rata-rata PSQI global pada pasien stroke masing-masing adalah 7,12±3,96 versus 4,98±2,86, lebih tinggi daripada kelompok non-stroke. Sekitar 56,7 persen pasien stroke mengeluhkan kualitas tidur yang buruk. Pasien stroke mendapat skor lebih rendah daripada mereka yang tidak terkena stroke pada tes memori dan fungsi eksekutif. Kualitas tidur mempengaruhi memori sebesar 28,6 persen. Kualitas tidur yang buruk sangat terkait dengan disfungsi memori pada pasien stroke. Untuk mencegah pasien stroke mengalami kehilangan kognitif, penyedia layanan kesehatan harus mengembangkan intervensi yang efektif untuk meningkatkan kualitas tidur.